Hippocampal volume in children with attention deficit hyperactivity disorder and speech and language delay - Vikas Dhikav; Manish Parakh; Kajal Pandey; Hemant Jangid; Pankaj Khicher (Annals of Indian Academy of Neurology, 2023)
Introduction: Hippocampus is a complex brain structure located deep in the temporal lobes of the brain. The structure has been implicated in several disorders related to cognition. Reports are emerging of its involvement in attention deficit hyperactivity disorder (ADHD). The current study was planned to assess the volume of the hippocampus in children with ADHD and speech and language delay with normal birth history using magnetic resonance imaging (MRI) of the brain. Material and Methods: MRI brain of 12 children (age range = 3–6 years) and 22 controls with clinical diagnosis of ADHD as per Diagnostic and Statistical Manual-5 were obtained in oblique coronal sequence (T1 weighted). The entire hippocampus formation was outlined manually using Image-J software available freely from www.freesurfer.com. Results were expressed as volume cubic millimeters ± SD. Results: Volumes of the hippocampi of children with ADHD were 2450.2 ± 667 mm3 (R) and 2505.8 ± 878.5 mm3 (L), respectively. The mean volume (bilateral) of the cases was 2478 ± 772.75 mm3. The right hippocampal volume of the controls was 3255.8 ± 1374.3 mm3 (R) and that of the left side was 3159.3 ± 1451 (L) mm3, respectively. Conclusion: Current study reported a substantial shrinkage (23%) of the left and right hippocampus in children with ADHD compared to controls.